ANALISIS IMPLEMENTASI GADAI TANAH PERTANIAN MENURUT UNDANG-UNDANG NOMOR 56 PRP TAHUN 1960 (STUDI DI KABUPATEN PONOROGO) - Akbar Ardya Putra; Rahayu Subekti; Purwono Sungkowo Raharjo (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study analyzes and examines the implementation of agricultural land pawning according to Law Number 56 PRP of 1960 in order to examine whether it has been effective or not in Ponorogo Regency. This research is included in the descriptive empirical research. Sources of data and types in this study are primary and secondary data. The approach applied in this research is a conceptual approach, a statutory approach and a sociological approach. The location chosen by the researcher for this research is Ponorogo Regency. Data collection techniques used are interviews and document and literature studies. The data analysis applied in this study was carried out qualitatively or descriptively. Looking at the development of the research carried out, the researcher can conclude that the implementation of pawning agricultural land in Ponorogo Regency has not been in accordance with Law Number 56 PRP of 1960. This happened because the people in Ponorogo Regency, which in general are rural communities, more often use customary law or customary law. verbal agreement on the implementation of the agricultural land pawn agreement because it is considered more efficient and easier in its implementation. So that the role of the government and the community is needed so that land pawn regulations can be effective, especially in Ponorogo Regency